Analisis Manajemen Risiko Pembiayaan Kepemilikan Rumah Syariah di Griya As-Sakinah Madiun - Qonita Qurrota A'yun; Ely Masykuroh; Luhur Prasetiyo (Institut Agama Islam Negeri Ponorogo, 2023)
The application of the concept of convenience triggers risks in Sharia KPR financing, such as problems with financing, cancellation of financing, delays in payment of material debts, delays in handing over buildings, and the risk of differences in land size. This qualitative field research aims to identify risks analyze the risk assessment of Sharia home ownership financing, the factors causing risk, and the risk management process in Sharia home ownership financing at Griya As-Sakinah PT Housing. Sabab Podho Moro Madiun. The data collection techniques used are observation, interviews, and documentation techniques. Researchers interviewed the developer (Director, Marketing Manager, Development Manager, Marketing Staff, Financial Administration Staff, Warehouse Administration Staff, and Engineering Team) and 3 (three) Griya As-Sakinah PT Housing users. Sabab Podho Moro Madiun. This research uses data analysis with an inductive method. The research results show Sharia house ownership financing at Griya As-Sakinah PT Housing. Sabab Podho Moro Madiun experiences several risks, namely financing risk, liquidity risk, operational risk, and compliance risk. Risk assessment of Sharia home ownership financing at Griya As-Sakinah PT Housing. Sabab Podho Moro Madiun is ranked 4th, namely high-fair—factors causing financing risks at Griya As-Sakinah Housing PT. Sabab Podho Moro Madiun comes from the developer (internal management processes, HR, and cash flow), and factors from the user (profitability, prospects, character, capacity, and user condition). The process of implementing risk management in PT. Sharia homeownership financing. Sabab Podho Moro has not fully implemented the risk management stages. The developer prioritizes the concept of flexibility and the principle of kinship towards users.